The effectiveness of context-based flashcard media on the reading and writing ability of Bima script of elementary school students in Rabakodo - Fauziah, Naila; Khatimah , Khusnul; Khairunnufus , Nastri (Universitas Ahmad Dahlan, 2026)
This study aims to evaluate the effectiveness of contextual-based flashcard media in improving the ability to read and write Bima script among elementary school students in Rabakodo Village, Bima Regency. The background of this study departs from the condition that learning Bima script in schools is still very limited, generally only relying on textbooks without media variations, so that students are less motivated and not able to read their local script properly. The research used a descriptive quantitative approach with a simple one group pretest-posttest design. The research subjects were 35 students in grades IV, V, and VI who were purposively selected from two elementary schools in Rabakodo. The instruments used were Bima script comprehension test, observation sheet, and documentation. Data were analyzed using normality test, paired t test, and effect size calculation. The results showed a significant increase in students' ability after learning with flashcards. The average pretest score of 24.25 increased to 81.20 on the posttest with p < 0.001 and a very large effect size (Cohen's d = 5.32). In addition to the increase in test scores, students also showed enthusiasm, active engagement, and higher learning motivation. Thus, contextual-based flashcard media proved effective in improving literacy in Bima script while contributing to the preservation of local culture.